2016
DOI: 10.1002/ijc.30472
|View full text |Cite
|
Sign up to set email alerts
|

Molecular heterogeneity of non-small cell lung carcinoma patient-derived xenografts closely reflect their primary tumors

Abstract: Availability of lung cancer models that closely mimic human tumors remains a significant gap in cancer research, as tumor cell lines and mouse models may not recapitulate the spectrum of lung cancer heterogeneity seen in patients. We aimed to establish a patient‐derived tumor xenograft (PDX) resource from surgically resected non‐small cell lung cancer (NSCLC). Fresh tumor tissue from surgical resection was implanted and grown in the subcutaneous pocket of non‐obese severe combined immune deficient (NOD SCID) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 50 publications
5
73
0
Order By: Relevance
“…Because patient-derived xenografts (PDX) closely mimic the molecular characteristics and heterogeneity of the original patient tumors, we further tested four cell lines cultured from early passage PDXs (PDX239, PDX277, PDX462 and PDX267) (24). Nine of the eleven cell lines achieved combination indices < 1.0, consistent with a synergistic response at nanomolar drug concentrations (Figure 1B; Supplemental Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Because patient-derived xenografts (PDX) closely mimic the molecular characteristics and heterogeneity of the original patient tumors, we further tested four cell lines cultured from early passage PDXs (PDX239, PDX277, PDX462 and PDX267) (24). Nine of the eleven cell lines achieved combination indices < 1.0, consistent with a synergistic response at nanomolar drug concentrations (Figure 1B; Supplemental Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence has shown that PDXs retain the genome-wide exomic nucleotide variants, gene copy number alterations, and DNA methylation patterns of their corresponding tumors [1][2][3][4] irrespective of the number of passages, 1,3 although clonal selection during initial engraftment and passaging of PDXs has been observed. They have been shown to recapitulate the histologic and genetic features of human primary tumors and to be useful in assessing treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…Although to our knowledge no such studies have been previously performed in the field of pediatric oncology, the low recapitulation of the proteomic landscape when MBLX was compared to primary MBL tumors is inconsistent with omics studies comparing xenografts of breast and colon cancers to their corresponding patient tumors (13,14). Our data, are in line with data derived from cell lines, that in previous comparisons to patient tumors have shown low correlation rates between their point-mutation frequencies, and marked differences in their mRNA and copy number profiles (15,16).…”
Section: Final Protein Database Of a Xenotransplanted Pediatric Medulmentioning
confidence: 99%